Creative visualization for dummies - Nixon, Robin, 1961- (--For dummies., 2011)
The secret to getting exactly what you want from life & mdash; from the man who has! A businessman who has built up, owned and sold software companies, a nightclub, a bed and breakfast (plus a couple of alehouses), author Robin Nixon knows that worldly success has little to do with the world. It begins with one's self & mdash;and one's deepest thoughts. When altered, your thoughts have the ability to impact your behavior and immediate universe, and, indeed, your destiny. Known as "Creative Visualization," this powerfully simple tool has adherents as well known as Oprah Winfrey. In Creative Visual.